Pengaruh Stres Kerja, Motivasi Kerja, dan Pengembangan Karir terhadap Kinerja Karyawan pada CV. Semesta Mendukung Indonesia (Semarang) - Dwi Haryanti, Restu; Kasmari, Kasmari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explain and assess the influence of work stress, work motivation and career development on the performance of CV employees. The Universe Supports Indonesia. This research applies quantitative methodology with a sample of 80 respondents. Sampling uses a saturated sampling technique or what can be called a census, where all members of the population are used as samples. Data analysis in this study used SPSS version 25.0. The results of this data processing are the results of the validity test, reliability test, f test, coefficient of determination test, and t test results. The results of the research can be concluded that work stress has a negative and insignificant effect on employee performance, work motivation has a negative and insignificant effect on employee performance, and career development has a positive and significant effect on employee performance.